Estudo de integração energética de rede de trocador de calor e emissão de gases de efeito estufa em processos industriais - Liem, Rosana Maria (Universidade Federal de São Carlos, 2013)
In light of the scientific evidence for global warming, the United Nations established the Framework Convention on Climate Change and defined the Kyoto Protocol that provided opportunities for sustainable social and economic development. The Clean Development Mechanism (CDM) is one of the protocols applicable to developing countries such as Brazil. Opportunities for industries to reduce greenhouse gas (GHG) emissions can be led by thermal energy integration studies. In addition, sustainable processes can result in energy savings as well as help to mitigate GHG emissions. This work presents a study of heat exchanger network (HEN) synthesis in order to reduce energy consumption and GHG emissions, and the benefits are evaluated in terms of energy savings and carbon credits for CDM projects. It was proposed to two case studies using HEN data from literature, one concerns burning fossil fuels, and other one was evaluated the bagasse combustion. Both studies were applied the Aspen Energy Analyzer® software and its performance of the design of the HEN employed the Automatic Retrofit and Automatic Recommend Designs features were evaluated too. GHG emissions were mitigated; the first case confirmed that the carbon credits improve Capital Expenditure Index, returning 13% less in payback depending on fossil fuel price. The second case presents a maximum value of reduction of 26.2% burning bagasse, 7.7% GHG emissions, 30% increase power generation, together with 19,411 carbon credits per year.
Keywords: Síntese; Trocadores de calor; Energia elétrica e calor - cogeração; Gases; Efeito estufa; Créditos de carbono; Síntese de rede de trocador de calor; Combustível fóssil e biomassa; Emissões de gases de efeito estufa; Mecanismo de desenvolvimento limpo; Análise financeira; Heat exchanger network synthesis; Fossil and biomass fuels; Cogeneration system; Greenhouse gas emission; Carbon credits; Clean development mechanism; Economic analysis; ENGENHARIAS::ENGENHARIA QUIMICA